Critical current measurement of commercial REBCO conductors at 4.2 K. (July 2017) - Tsuchiya, K.; Kikuchi, A.; Terashima, A.; Norimoto, K.; Uchida, M.; Tawada, M.; Masuzawa, M.; Ohuchi, N.; Wang, X.; Takao, T.; Fujita, S.
Highlights: Ic measurement holder, which accept U-shaped 4-mm wide REBCO wires, was developed. Ic values of the full-width REBCO wires were investigated at 4.2 K in B⊥ = 0.5–18 T. Ic properties of commercial REBCO wires from seven manufacturers were compared. High-current 4-mm wide wires have non-Cu Jc of 1000–2000 A/mm 2 at 4.2 K in an B⊥ =18 T. Abstract: REBCO coated conductors are now available from several industrial manufacturers and are expected to be promising conductors for high-field-magnet applications. Using these conductors, the development of solenoids capable of generating high magnetic fields of 20–30 T is ongoing in major high-field laboratories in the world. In addition, CERN recently launched a conceptual design study for the Future Circular Collider, in which a 20-T dipole magnet is listed as a candidate for the bending magnet of the main ring. However, there has been limited research published on the electrical transport properties of commercially available REBCO conductors in a high-field, low-temperature environment. For magnet designers, the transport properties are of the highest importance in choosing a suitable conductor, and the data form the bases for high-field magnet development. Therefore, in this work, a new sample holder, which allows the measurements of full-width conductors to be carried out relatively easily, was developed, and the transport properties of commercial REBCO conductors from seven manufacturers (AMSC, Fujikura, Shanghai Superconductor, SuNAM, SuperOx, SuperPower, and SWCC Showa) were investigated at 4.2 K in perpendicular fields of up to 18 T. The results show that the Ic values at 4.2 K clearly vary to some extent among these commercial conductors and the higher-current 4-mm-wide conductors have Ic values in the range of 230–305 A at 18 T and in the range of 320–424 A at 12 T.